Anmeldelser - Jacobsen, Niels Kingo; Jensen, Ruth Helkiær (Geografisk Tidsskrift, 1966)
Litteraturanmeldelser: FYSISK GEOGRAFI m.m. Melchior: The Earth Tides (S. Christiansen) ............................... 107 Ahrens, Press, Runcorn & Urey: Physics and Chemistry of the Earth (K. Hansen) ........................................................... 107 Lee: Terrestrial Heat Flow (K. Hansen) ................................... 107 Cissarz: Allgemeine und systematische Lagerstättenlehre (K. Hansen) . ... 107 Schmidt: Geologie (K. Hansen) ............................................ 108 Griffiths & King: Applied Geophysics for Engineers and Geologists (B. Fristrup) ......................................................... 114 Rankama: The Precambrian II (K. Hansen) .............................. 108 van Straaten: Deltaic and Shallow Marine Deposits (K. Hansen) .......... 108 Dzulynski & Walton: Sedimentary Features of Flysch and Greywackes (K. Hansen) ............................................................ 108 Lattman & Ray: Aerial Photographs in Field Geology (R. H. Jensen) ..... 113 Cotter: Physical Geography of the Oceans (S. Christiansen) ............... 110 Sears: Progress in Oceanography 3 (S. Christiansen) ...................... 110 Bezrukov: Geographical Description of the Bering Sea (S. Christiansen) . . . . 110 Nairn: Problems in Palaeoclimatology (B. Fristrup) ..................... 114 Byers: Elements of Cloud Physics (Kr. M. Jensen) ........................ 108 Sellers: Physical Climatology (Kr. M. Jensen) .......................... 109 Borisov: Climates of the USSR (Kr. M. Jensen) .......................... 109 Lück: Feuchtigkeit (Kr. M. Jensen) ........................................ 123 Scamoni: Beiträge zur Vegetationskunde VI (Kr. M. Jensen) ............ 109 Keller: Gewässer und Wasserhaushalt des Festlandes (S. Rasmussen) . ... 125 Cooper: Practical Land Drainage (S. Rasmussen) ........................ 110 KULTUR- OG ERHVERVSGEOGRAFI Coon: Origin of Races (C. G. Feilberg) ................................... 91 Day: Guide to Fossil Man (C. G. Feilberg) ................................. 94 East: Geography behind History (V. Hansen) ............................... 104 Thorkild Hansen: Jens Munk (R. H. Jensen) ............................... 112 Haggett: Locational Analysis in Human Geography (H. Johnson) ........ 121 Clarke: Population Geography (R. H. Jensen) ............................. 112 Beaujeu-Garnier: Geography of Population (L. Castro Lopo) .......... 117 Kirby: Vegetable Fibres (V. Hansen) ..................................... 116 Peterson: Wheat (V. Hansen) .............................................. 116 Best & Gasson: Changing Location of Intensive Crops (V. Hansen) ........ 116 EUROPA OG SOVJETUNIONEN Kristensen: Gamle sydvestjyske fiskerlejer (N. H. Jacobsen) ............ 120 Bergling: Kyrkstaden i ovre Norrland (C. G. Feilberg) ..................... 94 Simpson: Coal and the Power Industries in Postwar Britain (N. Nielsen) 105 Murray: The Hebrides (Aa. H. Kamp) ..................................... 120 McIntosh & Marshall: The Face of Scotland (V. Hansen) ................. 123 Elhai: La propriété fonciére des citadins en Haute-Normandie (V. Hansen) 105 Graber: Lebendige Vielfalt der Schweiz (V. Hansen) ..................... 106 Howald: Schweizerische Landwirtschaft und Schweizer Bauerntum (V. Hansen) .......................................................... 106 FREMMEDE VERDENSDELE Wright: The Elizabethan’s America (N. Nielsen) .......................... 90 Thornbury: Regional Geomorphology of the United States (V. Hansen) . . . . Ill Estall: New England (V. Hansen) ....................................... 120 Malaurie & Rosseau: Le Nouveau-Québec (V. Hansen) ................... 123 Robinson: Peru in Four Dimensions (Aa. Aagesen) ...................... 104 Cole: Latin America (Aa. Aagesen) ....................................... 119 Bovill: Missions to the Niger I (C. G. Feilberg) ........................... 96 Hatch: History of Postwar Africa (C. G. Feilberg) ...................... 96 Hance: Geography of Modern Africa (C. G. Feilberg) .................... 97 Yudelman: Africans on the Land (C. G. Feilberg) ........................ 98 Heidermann & Kühn: Afrikas Gegenwart und Zukunft (H. Jeppesen) . ... 98 Molnos: Die sozialwissenschaftliche Erforschung Ostafrikas (H. Jeppesen) 99 Fliedner: Die Bodenrechtsreform in Kenya (H. Jeppesen) ................. 99 Gray: The Sonjo of Tanganyika (C. G. Feilberg .......................... 99 Scudder: Ecology of the Gwembe Tonga (C. G. Feilberg) ................. 100 Cope: South Africa (R. H. Jensen) ....................................... 101 Jürgens: Binnenwanderung und Bevölkerungsentwicklung in Liberia (H. Jeppesen) ......................................................... 118 Hallett: People and Progress in West Africa (H. Jeppesen) ............... 118 Stratton: Madagascar (C. G. Feilberg) ................................... 100 Schattner: The Lower Jordan Valley (H. Kuhlman) ..................... 113 Bémont: Quelques problémes économiques de IT,ran (C. G. Feilberg..... 102 de Planhol: Geographie humaine de 1’Iran septentrional (C. G. Feilberg) . . 101 Rushbrook Williams: Handbook for Travellers in India, Pakistan, Burma and Ceylon (K. Hansen) .............................................. 103 Sievers: Ceylon (C. G. Feilberg)............................................ 102 Tregear: Geography of China (V. Hansen) .............................. 103 Allen: Japan’s Economic Expansion (S. Christiansen) ..................... 103 POLAREGNENE Hatherton: Antarctica (B. Fristrup) ........................................ 114 Billing & Mannering: South. Man and Nature in Antarctica (B. Fristrup) . . 115 Armstrong: Russian Settlement in the North (B. Fristrup) ............... 115 Michael: Siberian Ethnogenesis (C. G. Feilberg) .......................... 115 Levin: Ethnic Origins of the Peoples of Northeastern Asia (C. G. Feilberg) 115 ATLASVÆRKER OG KORT McGraw-Hill International Atlas (N. Nielsen) ............................ 89 Atlas of South-East Asia (N. Nielsen) ..................................... 90 Lister: How to Identify Old Maps and Globes (lb Kejlbo) ................. 91 NYE TIDSSKRIFTER m. m. Nordfriesland (N. Nielsen) ................................................ 125 Mare Balticum (N. Nielsen) ............................................... 125 Engineering Geology (N. Nielsen) .......................................... 126 LÆRERBØGER, SYMPOSIER m. ni. Monkhouse: A Dictionary of Geography (N. Nielsen) ...................... 91 Shaw: Fundamentals of Geography (8. Rasmussen) ....................... 124 Ghorley & Haggett: Frontiers in Geographical Teaching (R. H. Jensen) . .. . 117 Unesco Source Book for Geography Teaching (N. Ringo Jacobsen) ........ 111 Experimental Cartography (R. H. Jensen) ................................. 106 Compte-rendu du Colloque Géographique Franco-Polonais (V. Hansen) . . 113 BØGER INDGÅET TIL REDAKTIONEN .................... 126